Utility of a Simple and Robust Flow Cytometry Assay for Rapid Clonality Testing in Mature Peripheral T-Cell Lymphomas. Issue 5 (31st January 2019) - Novikov, Natasha D; Griffin, Gabriel K; Dudley, Graham; Drew, Mai; Rojas-Rudilla, Vanesa; Lindeman, Neal I; Dorfman, David M
Abstract: Objectives: Flow cytometry immunophenotyping is limited by poor resolution of T-cell clones. A newly described antibody was recently used to distinguish normal peripheral blood T cells from malignant T-cell clones. Here, we evaluate this antibody as a new diagnostic tool for detecting T-cell clonality in mature peripheral T-cell lymphomas. Methods: Immunostaining for the T-cell receptor β chain constant region 1 (TRBC1) along with routine T-cell markers was performed on 51 peripheral blood and two bone marrow samples submitted to the flow cytometry laboratory for suspected T-cell malignancy. Results: TRBC immunophenotyping identified malignant T-cell clones with 97% sensitivity and 91% specificity. Findings correlated with molecular T-cell clonality testing. In cases with equivocal molecular results, TRBC1 immunophenotyping provided additional diagnostic information. Conclusions: TRBC1 flow cytometric immunophenotyping is a robust and inexpensive method for identifying T-cell clonality that could easily be incorporated into routine flow cytometric practice.